ANALISIS SUDUT SERANG TERHADAP KARAKTERISTIK AERODINAMIKA PADA BILAH 4412 RPM RENDAH DENGAN METODE CFD 6DOF - Danang Febriyanto; Hangga Wicaksono; Bayu Pranoto; Mochamad Muzaki (Otopro, 2023)
At this time the power plant still uses a lot of coal fuel, so it is necessary to look for alternative energy, one of which is wind energy. Wind turbines are devices that can convert kinetic energy in the wind into mechanical energy which is then converted into electrical energy through a generator. The analysis method in this research uses Computational Fluid Dynamics (CFD), Qblade, and experimental validation testing using a wind tunnel. The simulated airfoil types consist of 3 types, namely, NACA 4412, NACA 4415, and FX-60 100 (126). The simulation results show that, the most optimal airfoil is NACA 4412 with an angle of attack of 25° and a wind speed of 8 m/s can produce a torque of 3.55503 Nm, a pressure of 45 Pa, a tangential velocity of 55.495 m/s, and a rotational speed of 529. 94 rpm, while the smallest simulation results are on the FX-60 100 (126) airfoil with an angle of attack of 15° and the same wind speed of 8m/s can produce a torque of 1.60390 Nm, a pressure of 40 Pa, a tangential velocity of 9.06592 m/s, and a rotational speed of 108.2164 rpm. The results of experimental testing of wind turbines where the wind turbine used uses the geometry of NACA 4412 show that an angle of attack of 25 ° and a wind speed of 8m / s produces a large electrical power and rpm with a value of 7.98 Watt and 482.2 rpm respectively